The cry of the excavator: notes on the social impact of urban renewal - Stefano Portelli (Informe Econômico (UFPI), 2022)
Many of the grassroot protests we witnessed to in the last years have put back to the center of our attention the issue of popular participation to urban planning. Therefore, it is now the moment to develop instruments that help us to evaluate public policies observing the short and long term effects they have on the populations that suffer them. The question of what are the consequences (individual or collective) of urban renewal is analized here in relationship to three fields of research: cultural anthropology, psychology, and urban studies. The limitations and potentialities of these three approaches are presented through the discussion on five texts (some of them classical, other not) in which different scholars developed different ways of studying the impact of urban renewal.FORRESTER, V. Uma estranha ditadura. São Paulo: Unesp, 2001.